Studies on the Effect of Salt Stress in rhizophora apiculata Bl. - T. Balasubramanian1*, P. Amuthavalli1, and P. Sivaraman2, S. Sivasankaramoorthy1 (Journal of Phytology, 2011)
The present study shows the effect of salt stress in the over all development of Rhizophora apiculata. The parameters used in this study were changes in growth morphology, biochemical constituents and photosynthetic pigments. From the study it was observed that the growth parameters such as root and shoot length, fresh and dry weight increased with increasing concentrations upto 400 mMÂ  NaCl. The organic compounds such as aminoacids and total sugar decreasedÂ  upto optimal level of 400 mM, but protein and starch increased upto the optimal level of 400 mM of NaCl salinity. The proline and glycine betaine increased upto the extreme level of 750 mM. So it is concluded that the photosynthetic pigments are upto the optimum concentration. <span style="line-height: 110%; font-variant: normal !important; font-family: ";Book Antiqua";,";serif";; letter-spacing: -0.3pt; font-size: 7pt; font-weight: normal; mso-fareast-language: EN-SG; mso-font-kerning: 0pt; mso-no-proof: no; mso-ansi-language: EN-SG;" lang="EN-SG">S.Sivasankaramoorthy et al. Studies on the Effect of Salt Stress in rhizophora apiculata Bl.. J Phytol 3/1(2011) 13-17.